Clinical heterogeneity of recessive ataxia in the Mexican population. Issue 12 (16th November 2006) - Rasmussen, A; Gómez, M; Alonso, E; Bidichandani, S I
Abstract : Approximately 75% of Indo-European patients with recessive ataxia are homozygous for frataxin gene ( FXN ) mutations and have either typical or atypical Friedreich ataxia (FRDA). Our previous analysis of 134 Mexican Mestizo recessive ataxia patients showed that FRDA is relatively uncommon in the Mexican population (10.4%). This article reports the evaluation of the phenotypes of these patients. Over half of the patients with clinical diagnostic criteria for FRDA did not carry FXN mutations, constituting a "FRDA-like" phenotypic subgroup. Analysis of non-FRDA patients revealed a subgroup with early onset recessive cerebellar ataxia and cognitive deficit. These two phenotypic subgroups accounted for approximately 60% of all patients, indicating that the cause for recessive ataxia in the Mexican population is distinct from other populations and remains largely unknown.